2004
DOI: 10.1094/cchem.2004.81.3.377
|View full text |Cite
|
Sign up to set email alerts
|

Grain Quality Characteristics and Milling Performance of Full and Partial Waxy Durum Lines

Abstract: Mutation of the gene coding for the granule bound starch synthase (waxy protein) leads to reduced amylose content in cereal endosperm. Durum wheat (Triticum turgidum L. var. durum) has one waxy locus in each of its two genomes. Full waxy durum wheat is produced when both genomes carry the waxy null alleles. When only one locus is mutated, partial waxy durum wheat is obtained. Partial and full waxy near‐isogenic lines of durum wheat developed by a breeding program were analyzed as to their quality characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
1
23
1
1
Order By: Relevance
“…Using nearisogenic lines produced after back-crossing to the durum cultivar 'Ben', Vignaux et al (2004) found no amylose in waxy lines but observed no reduction in amylose content in partial waxy lines. Vignaux et al (2005), using DSC, found waxy starch melting temperatures to be higher than partial waxy and wild-type starches, with both higher onset and final temperatures of the melting profile.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Using nearisogenic lines produced after back-crossing to the durum cultivar 'Ben', Vignaux et al (2004) found no amylose in waxy lines but observed no reduction in amylose content in partial waxy lines. Vignaux et al (2005), using DSC, found waxy starch melting temperatures to be higher than partial waxy and wild-type starches, with both higher onset and final temperatures of the melting profile.…”
Section: Introductionmentioning
confidence: 92%
“…durum) and other tetraploid wheats, one each by the Wx-A1 and Wx-B1 loci (Yamamori et al, 1995). Fully waxy (amylose-free) and partial waxy (reduced amylose) genotypes have been produced in durum wheat (Delwiche et al, 2006;Sharma et al, 2002;Vignaux et al, 2004). Partial waxy types contain a non-functional (null) gene at one of the two Wx loci.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Полученная тенденция, вероятно, связана с развлетвленной струк-турой амилопектина, способствующей замедлению перемещения влаги из внутренних слоев изделий к поверхности под действием градиента температуры и влажности. Также замедление потери влаги по сравне-нию с контролем для пряников на основе МПВ может быть связано с увеличением количества поврежден-ных зерен крахмала при ее внесении [21], что, в свою очередь, за счет их более высокой гидрофильности, способствует увеличению количества связанной воды в изделиях. Необходимо отметить, что на динамику изменения влажности сырцовых пряников в процессе хранения существенное влияние оказывает и более низкая температура клейстеризации крахмала беза-милозной муки по сравнению с ХПМ [22].…”
Section: влияние муки пшеницы вакси на изменение качества сырцовых прunclassified
“…The wheat hardness is strongly associated with the semolina and flour yields (Hrušková et al 2008). However, Vignaux et al (2004) reported hardness as possible cause for reduction in flour yield. Soft-textured wheat genotypes (Pina-D1a/Pinb-D1d) showed the least value for grain hardness and higher break flour and lesser reduction flour yield (Ma et al, 2009).…”
Section: Introductionmentioning
confidence: 99%